Managerial Roles in SMEs and Their Effect on Perceived Managerial Effectiveness in Lithuania - Diskienė, Danuta; Tamaševičius, Virginijus; Kalvaitytė, Agnė (Organizations and Markets in Emerging Economies, 2018)
The aim of this study was to analyze the managerial work of Lithuanian managers in terms of managerial roles and their effect on perceived effectiveness of managers’ work in small and medium – sized companies in Lithuania. Literature analysis reveals the concept of managerial work in terms of roles played by managers and discusses the issue of managerial effectiveness. Both concepts are seen as highly complex phenomena where role accomplishing is recognized as an important influential factor in effective managerial work performance. A survey was used as the most appropriate tool for data collection. The respondents at managerial positions were randomly selected in SMEs in Lithuania. Exploratory factor analysis was used to single out managerial roles, and multiple regression analysis was conducted to identify the relationship between managerial roles and perceived managerial effectiveness. The study revealed significant results in terms of performance of managerial roles and questioned the universalistic model of managerial roles by pointing out to their sensitivity to organizational context. The results demonstrate that a part of the activities of managers still fall within the framework of the traditional managerial roles. Yet, findings also suggest that there is a substantial part which can be subsumed under the new separate roles as Analyzer, Representor, and Networker. Regrouped managerial roles revealed a strong positive correlation with perceived managerial effectiveness.